О выборе координат размещения точек доступа в Wi-Fi сети - Шостак, А. В.; Дорошенко, Юрий Иванович (НТУ "ХПИ", 2015)
Проанализированы два различных подхода к оптимизации взаимного расположения двух точек доступа в Wi-Fi сети с целью максимизации суммарной скорости передачи данных двумя группами абонентов посредством выбора координат двух точек доступа. Рассмотрено влияние способов расположения точек доступа, размеров области расположения абонентов и количества абонентов на суммарную скорость приема/передачи абонентов сети, при этом решалась задача разбиения n абонентов на две равные (с точностью до 1) части.

There have been analyzed analyzed two different approaches to optimize the relative position of two access points in a Wi-Fi network to maximize the total data rate of the two groups of abonents by selecting the coordinates of two points of access. There have been solved the problem of partitioning n abonents into two equal part (to within 1). Proposed two ways of its implementation: – the rectangle formed by the minimum and maximum coordinates of abonents is divided into two parts, equal to the number of abonents in each part; – partitioning n abonents into two approximately equal parts abonents n nodes of an undirected graph is constructed Hamiltonian cycle of minimum length.
About choosing the location coordinates of access points in a Wi-Fi network
Keywords: оптимизация; расположение; диапазон; частота; моделирование; optimization; location